Gaussian fluctuation field of electrical polarization in strongly heated dielectric media - Virchenko, Yu.P.; Saprykin, M.A. (Вопросы атомной науки и техники, 2012)
The spatially nonuniform gaussian random field which describes fluctuations of electrical polarization in dielectric medium is built. It is done for the case when the space temperature distribution exists. This filed is the source of the thermal electromagnetic field by which the thermal radiation conduction is realized. Построено пространственно неоднородное гауссовское случайное поле, которое описывает флуктуации электрической поляризации среды при наличии пространственно неоднородного распределения температуры. Это поле служит источником теплового электромагнитного поля, посредством которого осуществляется радиационно-кондуктивный теплообмен. Побудовано просторово неоднорідне гауссівське випадкове поле, яке описує флуктуації електричної поляризації середовища у випадку, коли існує просторово неоднорідний розподіл температури. Це поле є джерелом теплового електромагнітного поля, завдяки якому діє фізичний механізм радіаційно-кондуктивного теплообміну.